Collaborations and Renegotiations Re-examining the 'Sacred' in the Film-Making of David Gulpilil and Rolf de Heer - Jasper, Alison E. (2017)
This article discusses the term 'sacred' in relation to the work of nineteenth-century sociologist Émile Durkheim, for whom the word denoted the objects, practices and assumptions that sustained communal solidarity and fostered dynamic energies, whether or not they were conventionally described as 'religious'. I then turn to the work of more recent scholars of 'critical religion' suggesting that the terms 'religion' and 'the sacred' derive from a predominantly western, patriarchal and colonial context, forming part of a complex network of interconnected categories that represent a distinctive and dominant discourse of power constructing a privileged identity through hostile Othering or exclusions. Arguably, in the Australian mainstream, a discourse of 'religion' imported largely by Christian settlers from the west over the last two hundred years has been employed to exclude Aboriginal ways of understanding the world, for example by promoting the category of 'land' as an exploitable, God-given human possession. Nevertheless, drawing on the work of Julia Kristeva, I understand that an encounter with the Other-whether the Aboriginal or the balanda-can be viewed differently: as a zone of properly disturbing but also creative possibility. It remains very important, however, to acknowledge the power imbalances that are still embedded within such encounters, and the consequent risks to indigenous Australians, of further dislocation and dispossession. This idea is explored through a consideration of the collaborative film-making of David Gulpilil and Rolf de Heer and, in particular, of two films: Ten Canoes (2006) and Charlie's Country (2013).